Brazilian Faculty and Student Perspectives on Excellent Teaching. (12th July 2018) - Henklain, Marcelo H. O.; Carmo, João S.; Haydu, Verônica Bender; Muniz, Monalisa
Abstract: We studied Brazilian faculty and psychology undergraduates' perspectives on excellent teaching using the Teacher Behavior Checklist. In two studies, we found that students and teachers showed strong agreement with those TBC items relevant to developing a profile of excellent teachers and that students valued some qualities more than others in terms of their contributions to excellent teaching, a finding consistent across different cultural contexts.